Seeing the landscape for the trees: metrics to guide riparian shade management in river catchments - Johnson, Matthew F.; Wilby, Robert L. (Wiley, 2015)
Rising water temperature (Tw) due to anthropogenic climate change may have serious consequences for river ecosystems. Conservation and/or expansion of riparian shade could counter warming and buy time for ecosystems to adapt. However, sensitivity of river reaches to direct solar radiation is highly heterogeneous in space and time, so benefits of shading are also expected to be site specific. We use a network of high-resolution temperature measurements from two upland rivers in the UK, in conjunction with topographic shade modelling, to assess the relative significance of landscape and riparian shade to the thermal behaviour of river reaches. Trees occupy 7% of the study catchments (comparable with the UK national average) yet shade covers 52% of the area and is concentrated along river corridors. Riparian shade is most beneficial for managing Tw at distances 5 to 20 km downstream from the source of the rivers where discharge is modest, flow is dominated by near-surface hydrological pathways, there is a wide floodplain with little landscape shade, and where cumulative solar exposure times are sufficient to affect Tw. For the rivers studied, we find that approximately 0.5 km of complete shade is necessary to off-set Tw by 1°C during July (the month with peak Tw) at a headwater site; whereas 1.1 km of shade is required 25 km downstream. Further research is needed to assess the integrated effect of future changes in air temperature, sunshine duration, direct solar radiation and downward diffuse radiation on Tw to help tree planting schemes achieve intended outcomes.